Time–frequency analyses of reaction times and theta/beta EEG ratio in pediatric patients with traumatic brain injury: A preliminary study. (3rd October 2017) - Gazzellini, Simone; Napolitano, Antonio; Bauleo, Graziella; Bisozzi, Eleonora; Lispi, Maria Luisa; Ardu, Eleonora; Castelli, Enrico; Benso, Francesco
ABSTRACT: Purpose : The literature on patients with attention deficit reports peculiar reaction time (RT) oscillation at very low frequencies (VLFO=0.06–0.2 Hz). The data were explained as default mode network (DMN) intrusion in goal-oriented activity. The present study investigates whether a pattern of recurrent lapses in attention can be detected in TBI patients and whether VLFO can be generalized to the sustained attention deficit, regardless of etiology. Methods : Groups of pediatric TBIs and healthy controls performed four attentional tasks. RT and theta/beta timeseries were subjected to wavelet analyses. Results : Significant high-power VLFOs were recorded in patient group performances but not in those of controls, both for RTs and theta/beta in all the tasks. Conclusion : This preliminary study suggests that central-midline theta/beta ratio could be considered a neurophysiological correlate of RT variability and that the general continuous goal-oriented activity can be cross-etiologically affected by recurrent lapses in attention regardless of the specific cognitive component involved.